Differential expression of TLR4 in patients of coronary artery disease with and without traditional cardiovascular risk factors. (25th January 2023) - Biswas, N; Roy, D; Karmakar, S; Bhowmik, R; Mazumdar, H; Banerjee, A; Roy, A; Dey, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Atherosclerosis is inherently an inflammatory process, with a complex interplay of inflammatory markers. It is established that these inflammatory markers play an important role in patients of Coronary Artery Disease(CAD) with traditional cardiovascular risk factors. However, the role of inflammation in the atherosclerotic process in patients of CAD without traditional risk factors is still not clearly known. Purpose: Our purpose was to determine whether in patients of CAD without traditional risk factors, TLR4(Toll like receptor 4) expression as a marker of inflammation is similar to that in patients of CAD with traditional risk factors. Materials and Methods: This observational cross sectional study was done between July'20 to Dec'21. Equal number of patients of CAD with and without traditional cardiovascular risk factors undergoing Coronary Artery Bypass Grafting (CABG) were enrolled. The risk factors considered were Hypertension, Diabetes, Dyslipidemia, Obesity and Addiction to Tobacco and/or Alcohol. A minimum of two punch biopsy samples of aortic tissue was taken from each subject undergoing CABG. Immunohistochemistry for TLR4, was done in Ventana BenchMark GX System. The primary TLR4 antibody was procured from reputed source. Results: The presence or absence of TLR4 expression was associated significantly with the Syntax scores (37.40±4.74 vs 29.5±8.71; p value=0.036), total Cholesterol (187±35.06mg/dL vs 130±35.69 mg/dL ;p value 0.010) and LDL cholesterol (118.86±28.12mg/dL vs 64.21±25.61 mg/dL; p value 0.003). TLR4 expression, however, was not significantly associated with the number of coronary vessels involved (p=0.298). TLR4 expression was also not significantly associated with any other individual risk factors. However, when the traditional risk factors were considered in combination, TLR4 expression was associated significantly with the number of risk factors present(p=0.029) the strongest being in those having 4 traditional risk factors. The level of TLR4 expression gradually declined with the decrease in the number of risk factors, having mostly weak or negative expression in patients without any traditional risk factors. Conclusion: Patients with CAD without any traditional risk factors, had a less severe coronary artery disease as manifested by lower Syntax scores, and had lower degree of TLR4 expression. Patients with CAD with traditional risk factors had more severe coronary artery disease as evidenced by higher Syntax scores, and had higher degree of TLR4 expression proportional to the number of traditional risk factors present. Thus, differential TLR4 expression in CAD patients with and without traditional risk factors indicated a difference in inflammatory state between the two groups and warrants further investigation. Different levels of TLR4 expression TLR4 expression and risk factors